PENGARUH ICT SELF EFFICACY TERHADAP TECHNOPRENEURSHIP INTENTION DIMODERASI OLEH ENTREPRENEURIAL ORIENTATION DAN MOTIVASI SISWA (Survey Pada Siswa Jurusan Teknik Komputer Jaringan SMK Negeri Di Kota Bandung) - Wulan Nur Fathonah, - (2021)
This research is based on the technopreneurship intention among student majoring in network computer and engineering at SMKN in Bandung. The purpose of this study was to analyze the effects of ICT self efficacy on technopreneurship intention and analyze moderating variable is entrepreneurial orientation and student motivation. The method used in this research is explanatory survey research with data collection techniques through questionnaires. The population of this research is 534 students majoring in computer network and engineering at SMK in Bandung while the sample of 224 students. The collected data is then analyzed using multiple linear regression analysis techniques with Moderate Regression Analysis (MRA). The result of this research is a)The intention of technopreneurship, ICT self efficacy, entrepreneurial orientation and students motivation in the category is very high, b)ICT self efficacy effect the intention of technopreneurship c)Entrepreneu-rial orientation effect the intention of technopreneurship d) student motivation effect the intention of technopreneurship e) There is an interaction between Entrepreneurial Orientation and ICT Self Efficacy on Technopreneurship Intention f) There is an interaction between Student Motivation and ICT Self Efficacy on Technopreneurship Intention. It is undeniable that student majoring in network computer and engineering at SMK in Bandung must have an high level of technopreneurship. So there are suggestions that students should have a tendency to innovate, be proactive and dare to take risks to start and manage businesses and to explore new business opportunities Keyword: Technopreneurship Intention, ICT Self Efficacy, Entrepreneurial Orientation and Student Motivation